Cluster size distributions in gas jets for different nozzle geometries. (20th June 2017) - Aladi, M.; Bolla, R.; Cardenas, D.E.; Veisz, L.; Földes, I.B.
Abstract: Cluster size distributions were investigated in case of different nozzle geometries in argon and xenon using Rayleigh scattering diagnostics. Different nozzle geometries result in different behaviour, therefore both spatial- and temporal cluster size distributions were studied to obtain a well-characterized cluster target. It is shown that the generally used Hagena scaling can result in a significant deviation from the observed data and the behaviour cannot be described by a single material condensation parameter. The results along with the nanoplasma model applied to the data of previous high harmonic generation experiments allow the independent measurement of cluster size and cluster density.